Political relations between the two division of the Red Sea 1803- 1840 - Al Sheikh, Manal Salem Obaid (Journal of Humanities & Social Sciences, 2018)
This study focuses on relations between the two parts of the Red Sea over different periods of time، And focus on the Saudi state on the one hand، compared to the African continent. The importance of the study by focusing on the intensity of interconnectedness throughout history in the relationship between the western part of the Red Sea with the eastern side، especially the Arabian Gulf، with emphasis on the fluctuation of this relationship by different ruling groups and control here and there. The research aims to identify the stages of development of the relationship between the two sides and the reasons for focusing on developing this relationship and attention to it. As well as factors that contributed to the prosperity of this relationship. This study has reached several conclusions. There is an historical importance of this relationship that no one can prevent.And that this relationship is complementary، and that the attempts of the great powers have been and are still in order to thwart this relationship and control the wealth on both sides and prevent third parties from obtaining it.
Keywords: the two parts of the Red Sea; the first Saudi state; the era of the call; the Salafist call; the Ottoman state